PENDIDIKAN KARAKTER DI SEKOLAH MENENGAH PERTAMA: PERAN ORANG TUA DALAM MENSUKSESKAN PENDIDIKAN KARAKTER - Fatihah, Husnul; Juliardi, Budi; Purnamalia, Trisa (UNTIRTA CIVIC EDUCATION JOURNAL, 2023)
The rapid development of globalization, with the complexity of challenges that must be faced by the younger generation, character education is a foundation that helps shape the personality and morality of individuals. This study aims to analyze the role of parents in the digital era in making character education a success in Junior High Schools. The research approach used is a qualitative approach and descriptive methods. Data collection was carried out through observation and literature studies. The results of the study stated that parents have a very significant role in making character education a success. Among the roles of parents are to provide role models to the entire school community as a manifestation of the implementation of the PPK program; support the implementation of the PPK program independently and cooperatively; support the implementation of intracurricular, co-curricular, and extracurricular activities based on PPK; support the implementation of the five-day school policy; carry out monitoring and evaluation of the implementation of the PPK program; and create a conducive home atmosphere in instilling character values. Some of these roles are still homework that needs to be improved, the decline in exemplary behavior from parents of students in interacting with teachers and the entire school community, the decline in the level of support from parents of students in character learning at school. Therefore, for the success of character education in junior high schools, parents of students should understand their roles, while on the other hand, teachers and the school community should also understand their respective roles.